Reforms In the Energy Sector – As A Leading Factor of Economic Stabilization in The New Uzbekistan - Kuchkarov Abdullo Vakhabovich (Genius Journals, 2021)
Socio-economic development of any society, the transformation of human capital as a result of practical actions are directly related to the activities of steadily growing sectors of the economy, starting, first of all, with micro-resources and small infrastructures of the same region, territory. In particular, along with such resources, today the need for sustainable development of the electric power industry, the energy sector has become a need of the time. Optimization of energy efficiency and consumption, which is safe and cost-effective, has become one of the main and urgent problems in international circles in recent years. The reason is that today, in the context of globalization, the economic and social integration of the energy industry is taking place all over the world, the need for which is rapidly increasing, as a result of which its share in the economy and the volume of consumption are also growing day by day. It is from this point of view that the wider introduction of innovative technologies into the industry, along with its further development, makes it necessary to save resources such as natural gas, oil, and coal.
Keywords: Economic Sectors; Growth; Electricity; Socio-Economic Development